Utility of GeneXpert in analysis of bronchoalveolar lavage samples from patients with suspected tuberculosis in an intermediate-burden setting. Issue 4 (October 2018) - To, Kin Wang; Kam, Kai Man; Chan, Denise Pui Chung; Yip, Wing Ho; Chan, Ka Pang; Lo, Rachael; Ng, Susanna; Ngai, Jenny; Lee, Shui Shan
Highlights: Bronchoalveolar lavage (BAL) fluid can be used for TB testing with GeneXpert. Specificity and sensitivity of GeneXpert TB test on BAL fluid are reasonably high. GeneXpert TB test plays a supplemental role in intermediate TB burden setting. TB culture remains important for diagnosis in GeneXpert negative cases. Summary: Objectives: To explore the clinical role of GeneXpert in managing pulmonary tuberculosis (TB) in an intermediate burden city. Methods: Sputum acid-fast-bacilli (AFB) smear negative patients underwent bronchoscopy for bronchial alveolar lavage (BAL). Fluids collected were examined for AFB smear, TB culture, TB polymerase chain reaction (PCR) (Cobas Taqman) and for GeneXpert. Results: From October 2015 to February 2017, 227 BAL samples were collected. Cough and haemoptysis were the presenting symptoms in 70.0% and 37.4%, respectively. Apical shadows on chest X-rays (CXR) and apical cavitations on computed tomography (CT) were commoner in GeneXpert positive cases ( p = 0.01 and 0.02, respectively). Sensitivity and specificity of GeneXpert for TB diagnosis was 80% and 98% respectively. Positive and negative predictive value of the test was 92.3 and 95.1%, respectively. There were 9 false negative GeneXpert samples (8 were Cobas Taqman TB PCR negative): 6 were diagnosed by BAL culture, 2 by biopsy and one by Cobas Taqman TB PCR. There were 3 false positive cases with negative culture; 2 were put on empirical treatment with favourable clinical responses, while one defaulted follow-p. Conclusion: GeneXpert in BAL samples has high sensitivity and specificity. It enabled timely initiation of anti-TB treatment in clinical suspicious cases.